2020
DOI: 10.1002/bit.27498
|View full text |Cite
|
Sign up to set email alerts
|

The assimilation of glycerol into lipid acyl chains and associated carbon backbones of Nannochloropsis salina varies under nitrogen replete and deplete conditions

Abstract: Mixotrophic cultivation can increase microalgae productivity, yet the associated lipid metabolism remains mostly unknown. Stable isotope labeling was used to track assimilation of glycerol into the triacylglyceride (TAG) and membrane lipids of Nannochloropsis salina. In N-replete media, glycerol uptake and 13 C incorporation into acyl chains were, respectively, 6-fold and 12-fold higher than in N-deplete conditions. In N-replete cultures, 42% of the carbon in the consumed glycerol was assimilated into lipid ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It was found that the hydrolytic action involves the activation of a catalytic triad following the formation of tetrahedral intermediates that stabilizes the enzyme structure (Yoshitake et al, 2009). Hydrolysis produced volatile fatty acids and glycerols that eventually assimilated by the microorganisms to yield lipid acyl chains for cell membrane maintenance (Poddar et al, 2020). Bacterial lipases are also recognized for breaking down plastic polymers like polyurethane (Gautam et al, 2007) and PET oligomers (Swiderek et al, 2022).…”
Section: Microbial Enzymes Involved In Biodegradation Of Synthetic Po...mentioning
confidence: 99%
“…It was found that the hydrolytic action involves the activation of a catalytic triad following the formation of tetrahedral intermediates that stabilizes the enzyme structure (Yoshitake et al, 2009). Hydrolysis produced volatile fatty acids and glycerols that eventually assimilated by the microorganisms to yield lipid acyl chains for cell membrane maintenance (Poddar et al, 2020). Bacterial lipases are also recognized for breaking down plastic polymers like polyurethane (Gautam et al, 2007) and PET oligomers (Swiderek et al, 2022).…”
Section: Microbial Enzymes Involved In Biodegradation Of Synthetic Po...mentioning
confidence: 99%